دور الحصيات الصفراوية الميكروية في التهاب البنكرياس مجهول السبب وذلك بالفحص المجهري للصفراء المستخرجة بتقنية الERCP - زيزفون, حسان; يازجي, هيثم; الأحمد, نذير (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: Microlithiasis diagnosed with microscopic examination of bile is an important reason for causing idiopathic pancreatitis, which justifies the need for endoscopic Retrograde Cholangiopancreatography (ERCP) in these patients with a sample of bile for microscopic study, and put the diagnosis and treatment necessary in order to prevent the recurrence of subsequent episodes of pancreatitis, and their high mortality and hospitalization. Aim: To identify the role of microlithiasis in idiopathic pancreatitis. Methods: A descriptive study of a series of cases involved 11 patients including 6 males and 5 females have pancreatitis diagnosed by abdominal pain with elevated serum amylase / lipase more than three times the normal limit with or without radial markers consistent with pancreatitis on CT or US, and which we couldn’t identify the reason of the disease in spite the traditional investigations. These patients were under gone ERCP and we collected a sample of bile during the procedure, and then studied under polarized microscopy after being centrifuged . The crystals of cholesterol monohydrate and calcium bilirubinate were considered the cause of idiopathic pancreatitis when their number was more than 5 crystals in the low magnification microscopic square. Results: We found that 45.5% of the cases had more than 5 crystals in the low-magnification microscopic area by microscopic examination of the bile and therefore it is likely that these crystals are the cause of pancreatitis in these patients. CONCLUSION: Microlithiasis are an important cause that can explain the occurrence of pancreatitis in a significant portion of patients whose conventional non-invasive laboratory and radiological diagnostic methods have failed to detect the cause of their pancreatitis. الحصيات الصفراوية الميكروية المشخصة بالفحص المجهري للصفراء سبب مهم متهم في إحداث التهاب البنكرياس مجهول السبب ما يبرر ضرورة إجراء تصوير للطرق الصفراوية والبنكرياسية بالطريق الراجع ERCP عند هؤلاء المرضى لوضع التشخيص والمعالجة اللازمة بغية منع تكرار نوب التهاب بنكرياس لاحقة مع ما تحمله من نسبة استشفاء ومواتية عالية. الهدف: التعرف على دور الحصيات الصفراوية الميكروية في التهاب البنكرياس مجهول السبب. المواد والطرق: دراسة وصفية من نوع سلسلة حالات شملت 11 مريض منهم 6 ذكور و5 إناث مشخص لديهم التهاب بنكرياس بوجود ألم بطني مع ارتفاع أميلاز/ ليباز المصل أكثر من ثلاثة أضعاف الحد الطبيعي مع أو بدون وجود علامات شعاعية تتماشى مع التهاب بنكرياس على الطبقي المحوري للبطن, والذين لم تنجح الدراسة المخبرية والشعاعية الروتينية لديهم من وضع سبب التهاب البنكرياس, تم إجراء تصوير للطرق الصفراوية والبنكرياسية بالطريق الراجع ERCP لهؤلاء المرضى مع أخذ عينة صفراء ومن ثم دراستها تحت المجهر المستقطب بعد تثفيلها, واعتبرت بلورات مونوهيدرات الكوليسترول و بيلوروبينات الكالسيوم متهمة بإحداث التهاب البنكرياس عندما يزيد عددها عن 5 بلورات في الساحة المجهرية منخفضة التكبير. النتائج: وجدنا أن 45.5% من الحالات لديها بالفحص المجهري للصفراء أكثر من 5 بلورات في الساحة المجهرية منخفضة التكبير وبالتالي يرجح أن هذه البلورات هي السبب في إحداث نوبة التهاب بنكرياس عند هؤلاء المرضى. الخلاصة: تعتبر الحصيات الصفراوية الميكروية سبباً مهماً يمكن أن يفسر حدوث التهاب بنكرياس عند قسم مهم من المرضى الذين لم تفلح طرق التشخيص المخبرية والشعاعية التقليدية غير الغازية بكشف سبب التهاب البنكرياس لديهم.